2015
DOI: 10.1128/aac.04843-14
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of pfmdr1 , pfcrt , pvmdr1 , and K13 Propeller Polymorphisms Associated with Plasmodium falciparum and Plasmodium vivax Isolates from the China-Myanmar Border

Abstract: bMalaria in the China-Myanmar border region is still severe; local transmission of both falciparum and vivax malaria persists, and there is a risk of geographically expanding antimalarial resistance. In this research, the pfmdr1, pfcrt, pvmdr1, and K13-propeller genotypes were determined in 26 Plasmodium falciparum and 64 Plasmodium vivax isolates from Yingjiang county of Yunnan province. The pfmdr1 (11.5%), pfcrt (34.6%), and pvmdr1 (3.1%) mutations were prevalent at the China-Myanmar border. The indigenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
7
35
2
Order By: Relevance
“…However, this mutation has been detected at a lower frequency and no correlation with treatment outcome has been observed. In Bangladesh, A578S mutation in the k13 propeller region has been reported, however, no data on clinical outcome are available [21]. A recent study has revealed that A578S mutation is commonly observed in Africa and is not associated with artemisinin resistance [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, this mutation has been detected at a lower frequency and no correlation with treatment outcome has been observed. In Bangladesh, A578S mutation in the k13 propeller region has been reported, however, no data on clinical outcome are available [21]. A recent study has revealed that A578S mutation is commonly observed in Africa and is not associated with artemisinin resistance [22].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular surveillance studies have greatly expanded the map of K13-propeller polymorphism to include additional areas of Cambodia [29], Thailand [30], Myanmar [31, 32], China [32, 33], and Bangladesh [34]; some of these mutations have been previously associated with slow parasite clearance at other sites, but most have not and require validation. Currently, C580Y predominates in Cambodia [22, 28, 29, 35, 36] and along the Thailand-Myanmar border [22, 28, 31], while F446I predominates along the Myanmar-China border [16, 31, 33].…”
Section: What Are the Genetic Determinants Of Artemisinin Resistance?mentioning
confidence: 99%
“…Luckily, there is a pipeline of more than 10 new antimalarial drugs in various stages, such as the new antimalarial compound OZ439 [32, 33]. Routine monitoring and surveillance, as recommended by the WHO Global Plan for Artemisinin Resistance Containment, should be strengthened [34]. Unfortunately, this study shows that artemisinin-based drugs are still the main focus for researchers in China [35].…”
Section: Discussionmentioning
confidence: 99%